Associations between Antibiotics for Non-tuberculous Mycobacterial Infection and Incident Sjögren's Syndrome: A Nationwide, Population-based Case-control Study. Issue 1 (December 2018) - Chao, Wen-Cheng; Lin, Ching-Heng; Chen, Yi-Ming; Hsu, Chiann-Yi; Chen, Jun-Peng; Chen, Hsin-Hua
Abstract This study aimed to address the association between the usage of antibiotics to treat nontuberculous mycobacteria (NTM) infection and the risk of Sjögren's syndrome (SS). We identified 5, 553 patients with newly diagnosed SS between 2002 and 2013 using Taiwan's National Health Insurance Research Database and compared them with 83, 295 non-SS controls matched (1:15) for age, sex, and the year of their first SS diagnosis. An increased risk of SS was found in patients receiving new macrolides (adjusted odds ratios (aOR) 1.95, 95% confidence intervals (CI) 1.80–2.11), fluoroquinolones (aOR 1.52, 95% CI 1.41–1.64), and tetracyclines (aOR 1.69, 95% CI 1.59–1.79) compared with non-SS controls after adjusting for the Charlson comorbidity index, bronchiectasis andHelicobacter pylori infection. Notably, the association was consistent among each antibiotic in these three groups of antibiotics. In contrast to these three groups of antibiotics, the use of amikacin tended to have a negative association with incident SS (aOR 0.68, 95% CI 0.53–0.87). In conclusion, new macrolides, fluoroquinolones and tetracyclines were associated with a higher incidence of SS. These findings indicate the need for vigilance of SS in prescribing these antibiotics and warrant further mechanistic studies.